EXTRAUMBILICAL SINGLE-INCISION LAPAROSCOPIC CHOLECYSTECTOMY WITH STANDARD LAPAROSCOPIC INSTRUMENTS - UĞURLU, MUSTAFA ÜMİT (SAGE PUBLICATIONS LTD, 2013)
Background and Aim: Single-incision laparoscopic surgery is a rapidly progressing field as it combines some advantages such as cosmesis and less incisional pain. However, it also has some disadvantages such as limitation of movement and clashing of the hand instruments, which increase the complexity and technical challenges of the operation. In this study, we describe a pilot trial of single-incision laparoscopic cholecystectomy through a paramedian access site. Material and Methods: A total of 25 patients underwent single-incision laparoscopic cholecystectomy with this method. Acute cases with empyema and patients with history of previous abdominal surgery were excluded. Single-incision is established on the right upper quadrant, right latero-superior of the umbilicus, so that trocar sites and projection of the gallbladder on the abdominal wall are on the same vertical line. Standard laparoscopic instruments were placed into the abdominal cavity providing triangulation. Once the laparoscope, grasper, and dissector are in place, the overall procedures are similar to the standard laparoscopic cholecystectomy. Results: Single-incision laparoscopic cholecystectomy through an extraumbilical access site was successfully completed in all 25 patients without conversion to open surgery. Additional skin incisions and trocar access were required only in two patients. The mean operative time was 39.3 min (range: 20-75 min). The mean body mass index was 27.2. Postoperative course was uneventful in all patients. The mean postoperative hospital stay was shorter than 24 h, and all patients were discharged at first day postoperatively. No postoperative complications including seroma, wound infection, and trocar-site hernia were observed at 6-month follow-up. Conclusion: We described a new access site for single-incision laparoscopic cholecystectomy using standard laparoscopic instruments. We believe that this type of access site overcomes the technical difficulties of performing single-incision laparoscopic cholecystectomy, and it is a promising alternative method for the treatment of patients with symptomatic gallstone disease as a minimal invasive abdominal surgery.
Keywords: Cholecystectomy; laparoscopy; single-incision laparoscopic surgery; SURGERY SILS; SITE LESS; PORT; METAANALYSIS; SPLENECTOMY; VIDEO